Training in psychotherapy in a network medical residency program in psychiatry - Generoso, Marcelo Bruno (2022)
In Brazil, training in psychotherapy in medical residency programs in psychiatry is mandatory, but there is no consensus on how it should be carried out. The format of the network medical residency program in psychiatry of the Municipal Health Department of São Paulo provides for a weekly theoretical course on basic concepts of psychology and psychotherapy in the first year and psychotherapy sessions during the second and third year in the various Basic Health Units. from the program. Supervision of care is carried out in groups once a week for a period of 4 hours by a team of psychologists.